PERANCANGAN TAMAN KANAK-KANAK DENGAN PENDEKATAN ARSITEKTUR HIJAU - Alde Apriansyah Winhartono; Ira Mentayani (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
This research examines the design of An-Nur Kindergarten with a green architecture approach in the PT. Hasnur Citra Terpadu area, Pandahan, Central Tapin, Tapin Regency. The study is driven by the lack of adequate educational facilities in palm oil and coal industrial areas, where distance to schools poses a major obstacle to early childhood education. The design methodology integrates green architecture principles with specific early childhood learning requirements. The results demonstrate that implementing green architecture concepts in An-Nur Kindergarten's design not only creates an optimal learning environment but also supports ecological sustainability through renewable energy systems and eco-friendly materials. This design successfully presents an architectural solution that combines educational needs, environmental awareness, and local socio-cultural integration.